Evaluation of methods of combating syphilis in Podlaskie Province in the years 1999-2007 - Jakubowski, Adam; Janczyło-Jankowska, Małgorzata; Soszka-Jakubowska, Maria; Chodynicka, Bożena (Dermatology Review/Przegląd Dermatologiczny, 2009)
Introduction. The principal methods used to combat syphilis include prophylactic serological tests for syphilis, epidemiological investigations to detect the source of infection and contacts, treatment (including prophylactic treatment of the patients’ contacts) and promotion of proper health behaviours. Objective. The aim of the study was to assess the methods used to detect and combat syphilis in Podlaskie Province in the years 1999-2007. Material and methods. The analysis involved 695,030 prophylactic serological tests for syphilis (psts), 129 patients with early syphilis and 139 of their contacts (including 83 named). Indices commonly accepted in the epidemiology of venereal diseases were used for the assessment. Results. A systematic drop in the number of prophylactic serological tests for syphilis performed (from 225,604 in 1998 and 130,339 in 1999 to 53,084 in 2007), in the percentage of the population examined (from 18.4 to 10.7 and 4.4%, respectively) and in the proportion of new cases detected with this method (from 47.8% in 1998 to 20% in 2007) was noted. 75/129 patients (58.1%) with early syphilis indicated 83 named contacts (index – 0.64), of whom 72 were examined (index – 0.86). In the tested group 23 new cases of syphilis were detected (efficacy index – 0.18 and epidemiological index – 0.31). Twelve asymptomatic patients (16.7%) negative at the first serological examination agreed to receive prophylactic treatment (index – 0.16). Fifty-five subjects (42.6%) reported to a venereal disease outpatient clinic on their own initiative, in 51 (39.5%) of them the infection was detected in psts whereas in 23 (17.8%) via epidemiological investigations. As compared to the previous years, the time from between notification of syphilis contacts to their examination was prolonged. Conclusions. The study revealed a systematically decreasing role of prophylactic serological tests in detection and prevention of syphilis spread. The findings showed low percentages of patients who reported contacts as well as low indices of the reported and examined contacts. The efficacy and epidemiological indices were decreased and so were those referring to the prophylactic treatment of contacts who were asymptomatic and serologically negative at the first examination. Our findings indicate the necessity to improve epidemiological investigations, coordination and supervision of the work done in venereal outpatient clinics as well as the need for wide promotion of proper health behaviours. This can be accomplished by reactivating the methodical and organizational divisions which were closed by the health care reform of January 1999, at the level of provincial dermatovenereal outpatient clinics operating in the capitals of provinces.